2011
DOI: 10.1074/mcp.m110.006650
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Human Myotubes From Type 2 Diabetic and Nondiabetic Subjects Using Complementary Quantitative Mass Spectrometric Methods

Abstract: Skeletal muscle is a key tissue site of insulin resistance in type 2 diabetes. Human myotubes are primary skeletal muscle cells displaying both morphological and biochemical characteristics of mature skeletal muscle and the diabetic phenotype is conserved in myotubes derived from subjects with type 2 diabetes. Several abnormalities have been identified in skeletal muscle from type 2 diabetic subjects, however, the exact molecular mechanisms leading to the diabetic phenotype has still not been found. Here we pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
36
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 70 publications
4
36
0
Order By: Relevance
“…Slow fibres are more oxidative and insulin sensitive than fast fibres . Our proteomic‐based observation that fast myosin (MHCIIa) expression is upregulated in diabetic myotubes is consistent with the idea that primary insulin resistance in myotubes may also be associated with loss of slow fibres, although we did not confirm a concomitant increase in slow myosin expression in lean myotubes. Currently, it is unknown to what extent fibres co‐expressing developmental and neonatal myosin represent more than a transitional stage in the development of mature muscle fibres .…”
Section: An Explanation Of the Concurrent Impairment Of Insulin‐stimusupporting
confidence: 42%
See 1 more Smart Citation
“…Slow fibres are more oxidative and insulin sensitive than fast fibres . Our proteomic‐based observation that fast myosin (MHCIIa) expression is upregulated in diabetic myotubes is consistent with the idea that primary insulin resistance in myotubes may also be associated with loss of slow fibres, although we did not confirm a concomitant increase in slow myosin expression in lean myotubes. Currently, it is unknown to what extent fibres co‐expressing developmental and neonatal myosin represent more than a transitional stage in the development of mature muscle fibres .…”
Section: An Explanation Of the Concurrent Impairment Of Insulin‐stimusupporting
confidence: 42%
“…. Utilizing day 8 cultures, we showed that basal glucose uptake is increased in diabetic myotubes compared to age‐matched lean myotubes ; however, GLUT1 expression did not differ between the diabetic and control myotubes .…”
Section: Insulin Resistance Is Preserved In Myotubes Established Frommentioning
confidence: 77%
“…Augmented phosphorylation of mitochondrial aconitase was associated with a reduced TCA cycle flux, based on an increased reverse activity, while the forward reaction was normal. That PTM could be part of the explanation for a reduced TCA cycle flux in diabetic mitochondria is supported by our previous finding of a 14% reduced citrate synthase activity in diabetic myotubes [12] which cannot be explained by changes in protein expression [15]. Additional phosphoproteomic studies are required to test whether the impaired TCA cycle flux, in diabetic mitochondria, is based on posttranscriptional modifications of TCA cycle enzymes.…”
Section: Discussionmentioning
confidence: 70%
“…There have been several previous approaches to the study of the human skeletal muscle proteome [13,14] and its alterations in insulin-resistant muscle [15][16][17][18]. Two studies have used the two-dimensional gel approach [15,16].…”
Section: Introductionmentioning
confidence: 99%